What if all children achieved WHO recommendations on physical activity? Estimating the impact on socioeconomic inequalities in childhood overweight in the UK Millennium Cohort Study. (7th December 2018) - Pearce, Anna; Hope, Steven; Griffiths, Lucy; Cortina-Borja, Mario; Chittleborough, Catherine; Law, Catherine
Abstract: Background: The World Health organization (WHO) recommends that children engage in 60 min daily moderate-to-vigorous physical activity (dMVPA). Just half of children in the UK achieve these levels (with similarly low levels in other high-income countries). Thus, the dMVPA target is a focus of national obesity strategies. However, the potential impact of increased physical activity on prevalence and inequalities in childhood overweight is unknown. Using objective data from the Millennium Cohort Study (∼18 000 children born 2000–02) we simulated a series of hypothetical physical activity intervention scenarios: achievement of the target, and more realistic increases demonstrated in trials. Methods: Predicted probabilities of overweight and obesity (using measured heights and weights at age 11) were estimated in multinomial marginal structural models, adjusting for dMVPA (measured with accelerometers at age 7) and confounding. Inequalities were assessed according to household income quintiles [risk ratios (RRs) and risk differences (RDs)]. Intervention scenarios were simulated by re-estimating predicted probabilities of overweight/obesity after manipulating (increasing) dMVPA by varying amounts, for different eligibility criteria and with varying uptake. Analyses included 6493 children with accelerometer data. Survey weights and multiple imputation addressed sampling design, attrition and item missingness. Results: In all, 27% children were overweight/obese, with relative and absolute inequalities in the expected direction; 51% children were achieving 60 min dMVPA, with those from the lowest income quintile achieving, on average, 3 min more dMVPA than those from the highest income quintile. A simulation of universal achievement of the dMVPA target reduced the prevalence of overweight/obesity to 22%, but increased relative inequalities (absolute inequalities were unchanged). Smaller increases in dMVPA (informed by intervention evidence) did little to reduce prevalence or inequalities, even when targeting high-risk groups. Conclusions: Universal achievement of the WHO dMVPA target, if attainable, would reduce prevalence of childhood overweight and obesity but not inequalities. Scale-up of more realistic interventions would have limited impact.